The Psychologist's Companion : A Guide to Writing Scientific Papers for Students and Researchers / [electronic resource] - Sternberg, Robert J.; Sternberg, Karin (Cambridge : Cambridge University Press, 2010)
The Psychologist's Companion is intended for students as well as young professionals and writers at all stages of their careers seeking inspiration and guidelines for better scientific writing. This book is also a resource for researchers in related fields. It has been comprehensively updated, revised, and extended for its fifth edition and includes the latest style guidelines of the American Psychological Association's Publication Manual (sixth edition, 2009) as well as chapters encompassing the entire research process from doing literature research and planning an experiment to writing the paper. It features new chapters on literature research; ethics; and generating, evaluating, and selling ideas. The Psychologist's Companion also provides information on writing book proposals, grant proposals, and lectures.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Report writing; Psychological literature